German Jews and the university, 1678-1848 - Richarz, Monika (Dialogue and disjunction, 2022)
Traces the gradual opening of university education in Germany to Jews, its significance for assimilation to the bourgeoisie, and the legal restrictions that nonetheless barred Jewish graduates from most professional careers